A fronteira do consumo: relações transfronteiriças entre Foz do Iguaçu (BR) e Ciudad del Este (PY) - Polon, Luana Caroline Künast (2014)
The present study uses concepts of geography and related fields to display the relationships which are established based on the consumption of goods in a specific environment listed in the case, the border between Brazil and Paraguay. The space is built daily through social relations, as well as these can also be influenced by the spatial configuration. The Contemporary society reproduces itself based on the consumption of goods and therefore the consumer relations have influences on the constitution of spaces. The border is simultaneously limit and approach and the transborder condition is related to the political and economic issues of the nations. Therefore, based on literature review, by newspaper media consultation and field job with interviews, this study analyzes consumer relations in the constitution of the border area and transborder relations between Brazil and Paraguay, specifically between the cities of Foz do Iguaçu and Ciudad del Este. Thereunto, the conceptual, historical and geographical aspects will be addressed, taking as premise the existence of a "border of consumption", which is recreated daily through of transborder consumer relations that are established in this. The research also points to the flexibility of this border environment and type of relationships and experiences that unfold therein, which depend on various factors, as the economic policies of the nation s constituent of the border, and this can be influenced by the economy and world politics. The study perceives that the boundary is presented in multiple ways, the first being the physical. The physical border is transposed through the link created, which is represented by elements of infrastructure. There is equally a cultural border, but this is also likely to porosity, so that devices are designed so that social relations are possible. This boundary of the representative consumer is in a consumerist society bases, and therefore, their vulnerability is dependent on this same society